Belief functions : theory and applications : 5th International Conference, BELIEF 2018, Compiègne, France, September 17-21, 2018, Proceedings /: theory and applications : 5th International Conference, BELIEF 2018, Compiègne, France, September 17-21, 2018, Proceedings. (2018) - Unknown
No abstract available